2000
DOI: 10.1148/radiology.215.1.r00ap34169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Luminance and Resolution on Observer Performance with Chest Radiographs

Abstract: At a resolution of 400-microm pixels or higher across the field of view and a luminance of 260 cd/m(2) or more, primary diagnosis with posteroanterior chest radiographs is not likely to be affected by the quality of display.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…Two studies have been reported on the effects of the luminance of a specially constructed viewing box [1] and the cathode-ray tube (CRT) monitor on observer performance with chest radiographs [2]. Herron et al [1] suggested that the brightness of the viewing box of 75 footlamberts (260 cd/m 2 ) or greater should be sufficient for a primary diagnosis of posteroanterior chest images.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have been reported on the effects of the luminance of a specially constructed viewing box [1] and the cathode-ray tube (CRT) monitor on observer performance with chest radiographs [2]. Herron et al [1] suggested that the brightness of the viewing box of 75 footlamberts (260 cd/m 2 ) or greater should be sufficient for a primary diagnosis of posteroanterior chest images.…”
mentioning
confidence: 99%
“…Herron et al [1] suggested that the brightness of the viewing box of 75 footlamberts (260 cd/m 2 ) or greater should be sufficient for a primary diagnosis of posteroanterior chest images. Goo et al [2] described that, when an adequate window width and an adequate level of soft-copy images are applied, a primary diagnosis of chest radiographs on a CRT monitor is unlikely to be affected under low ambient light and at a monitor luminance of 25 foot-lamberts or more.…”
mentioning
confidence: 99%
“…With a lower level of luminance, certain lesions, particularly pneumothorax, interstitial lung disease, and rib fracture, may be poorly demonstrated (Herron et al 2000 ). Ambient light should be maintained at a lower level than typical offi ce lighting.…”
Section: Chest Radiograph Observer Errors Due To Displaymentioning
confidence: 99%
“…With digital and PACS systems, soft copy images are displayed on the workstation. Detection The patient also has a right subpulmonic effusion of interstitial lung disease or rib fracture warrants adequate luminance of the workstation monitor, while detection of pneumothorax requires both luminance and high-resolution monitor (Herron et al 2000 ). The disadvantages of cathode ray tube (CRT) and liquid crystal display (LCD) monitors are that these provide less luminance than a view box.…”
Section: Chest Radiograph Observer Errors Due To Displaymentioning
confidence: 99%
See 1 more Smart Citation